REPLACEMENT OF SOFTWOOD KRAFT PULP WITH ECF-BLEACHED BAMBOO KRAFT PULP IN FINE PAPER - Guanglei Zhao (BioResources, 2010)
Non-wood fibers such as bamboo and wheat straw have been playing important roles in the pulp and paper industry in China. In this study an ECF-bleached bamboo kraft pulp was compared with a bleached softwood kraft pulp (NBSK) as the reinforcement pulp in fine paper production. Areas that were examined include the refining of pure fibers, influence of bamboo on dewatering, retention, and sizing. The influence of bamboo kraft pulp as a part of a furnish replacing NBSK was compared as well. Results show that fiber shortening was more prominent with bamboo when refined. This resulted in a higher amount of fines, and addition wet-end chemicals may be required to compensate. Handsheets with bamboo as a reinforcement fiber showed similar mechanical and optical properties to handsheets containing NBSK.